Synthesis and characterization of oil sorbent based on Hydroxypropyl Cellulose Acrylate - Mohamed Keshawy; Thanaa Abd El-Moghny; Abdul-Raheim M. Abdul-Raheim; Khalid I. Kabel; Sabrnal H. El-Hamouly (Egyptian Journal of Petroleum)
The present work deals with the preparation of some oil sorbers based on cellulose derivatives to control petroleum oil spills. In this respect, hydroxypropyl cellulose HPC was used to synthesize hydroxypropyl cellulose acrylate HPCA macromonomer by esterification of HPC with acryloyl chloride. Then the produced HPCA monomer was copolymerized with octadecyl acrylate (ODA) in the presence of two types of crosslinkers to produce oil gel. The chemical structures of both HPC and HPCA were confirmed by using FTIR and 1HNMR spectroscopic analysis. Whereas the thermal properties of the crosslinked oil absorbents were investigated using TGA. Furthermore, morphological properties of prepared crosslinked copolymers were studied using SEM. Several parameters were considered to evaluate the oil sorbers, such as: monomers feed ratio, type and concentration of the applied crosslinkers. Finally, the swelling efficiency of oil gel was thoroughly investigated in light and heavy oil. It observed that as the octadecyl acrylate content increased the oil absorbency also increased and reached a maximum value at monomer feed ratio 10/90 HPCA/ODA. It is found that the maximum oil absorbency measured with MBA at a monomer feed ratio 10/90 HPCA/ODA are 29.7 and 18.6 g/g for toluene and crude oil, respectively.